Efficiency of Public Procurement in Magelang City Government: A Comparative Analysis - Sadono, Madu; Wijaya, Andy Fefta; Wanto, Alfi Haris; Fujimoto, Koji (Jurnal Ilmiah Administrasi Publik, 2017)
This study aims to find out the public procurement process before and after the implementation of e-procurement in Magelang City Government and to assess whether the implementation of e-procurement has been or not improved in Magelang City Government. This study investigates cost efficiency, time efficiency and other aspect of efficiency in comparison with conventional procurement. This comparative study is useful to explain the procurement process before and after the implementation of e-procurement. The implementation of public procurement using e-procurement is more efficient compared with conventional procurement. There are problems that hinder the process of public procurement. The problem in the implementation of procurement in Magelang City is human resources. These problems prevented improvements in procurement in Magelang City.